PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMPN 13 MATARAM TAHUN AJARAN 2023/2024 - Faridah, Siti Jaizah; Hikmah, Nurul; Kurniawan, Eka; Azmi, Syahrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted to determine the effect of cooperative learning model type think talk write (TTW) on mathematical communication skills in students of SMPN 13 Mataram class VIII on statistics material. Quantitative approach with quasi experimental method was used in this research. The population in this study were all VIII grade students of SMPN 13 Mataram consisting of five classes, with a sample consisting of two classes, namely class VIII E as an experimental class using the cooperative learning model of think talk write (TTW) type and class VIII A as a control class using direct learning model. Data collection techniques used observation sheets, documentation, and tests. The results of data analysis showed that there was an average difference between the experimental and control classes. The t-test results obtained a calculated t-value of 2.939, and the critical t-value obtained a value of 2.645, the result indicate the calculated t-value is greater than the critical t-value. So that the Think Talk Write (TTW) type cooperative learning model affects students' mathematical communication skills.